Biofilm reduction potential of micro-plasma discharged water (m-PDW) against the microbes isolated from a tofu manufacturing plant. (November 2018) - Kim, Mi-Hyun; Khan, Muhammad Saiful Islam; Lee, Kwang-Won; Kim, Yun-Ji
Abstract: In this study, biofilm inactivation potential of micro-plasma discharged water (m-PDW), a commercially available water purifier known as EP purification, was evaluated. Bacterial strains were collected from the various contaminated area of tofu manufacturing industry, overall 15 different types of bacterial strains were isolated and their biofilm formation ability was determined by using crystal violet (CV) staining. Three different strains (20% of the isolated strains), namely, Brevundimonas naejangsanensis, Delfita lacustris and Lactococcus lactis, with biofilm density (OD590 ) > 0.4, were identified as biofilm-producing strains. These three biofilm-producing strains were used to form biofilm on stainless steel (SS) coupons in a laboratory condition for four days and the biofilm containing coupons were treated with EP purification device. The inactivation obtained after 40 min of treatment was 4.8 and 4.2 log CFU/coupon for Brevundimonas naejangsanensis and Delfita lacustris, respectively, whereas no viable count was detected for Lactococcus lactis after the same treatment time. Biofilm reduction effects of m-PDW treatment differ according to biofilm-producing ability or strain characteristics. SEI (Secondary Electron Images) was obtained by field emission scanning electron microscope (FE-SEM) that showed m-PDW treatment has significant reduction potential on biofilm inactivation for the sample collected from tofu manufacturing industry. Highlights: Three different biofilm-forming strains were isolated from tofu manufacturing industry. EP purification device has a great potential for biofilm inactivation. Different strain has different surviving ability against micro-plasma discharged water treatment.